Multiaxial fatigue life prediction method of notched specimens considering stress gradient effect. Issue 5 (21st February 2021) - Liu, Jianhui; Ran, Yong; Xie, Linjun; Xue, Wenzhuo
Abstract: This paper investigates the effect of stress gradient on the fatigue life of U‐notched specimens under multiaxial proportional loading by studying the shear stress gradient and normal stress gradient on the crack initiation plane separately. First, based on the energy method and critical plane method, an energy‐critical plane method for determining the direction of crack initiation is proposed. Second, with the help of the concept of stress field intensity, the shear stress gradient and normal stress gradient on the critical plane are studied. Finally, a multiaxial fatigue life prediction model is established by combining the equivalent stress field intensity, composed of the shear stress field intensity and normal stress field intensity, with the Manson–Coffin equation. Theoretical analysis is verified by the experiments of Q345 steel notched specimens, and the results show that the predicted accuracy of the proposed method is not conservative and is superior to the local stress–strain method.